The Classification of Bambusa spp. from Celebes Based on the Micromorphological Characters of Leaf Epidermis - Alin Liana; Purnomo Purnomo; Issirep Sumardi; Budi Setiadi Daryono (Journal of Tropical Life Science, 2017)
Species of Bambusa had widespread in Celebes, especially for Bambusa striata and Bambusa vulgaris. As an effect of the lacking of flowering, species identification mainly depends on vegetative features, and leaf epidermal micromorphology has proven to be useful in bamboo taxonomy. The objective of this research was to describe the classification of Bambusa from Celebes based on the micromorphological characters of leaf epidermis. The specimens were collected from wild population. The samples of leaf were collected from five member of Bambusa i.e.: Bambusa blumeana, Bambusa maculata, B. striata, B. vulgaris and Bambusa sp. Micromorphological characters were identified using Scanning Electron Microscopy (SEM). Leaf epidermis characters separated B. blumeana from other species of Bambusa. Furthermore, B. striata were closely related to B. maculata in variation of bulliform cells. As an invention, we release peltate hair as a new type of trichome in Bambusa. The presence of various prickles, trichomes and bulliform cells may be especially useful in delimiting species.